1981
DOI: 10.1093/oxfordjournals.jbchem.a133342
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Inhibition by Methionine and S-Adenosylmethionine, and Desensitization of Homoserine O-Acetyltransferase in Brevibacterium flavum

Abstract: Homoserine O-acetyltransferase [EC 2.3.1.31] partially purified from Brevibacterium flavum was found to be specifically inhibited by the metabolic end products methionine and S-adenosylmethionine only when the enzymatic reaction was performed in the presence of cysteine or dithiothreitol, or after the preincubation of the enzyme with either of the sulfhydryl compounds. p-Hydroxymercuribenzoate desensitized the enzyme to inhibition. Concentrations of methionine and S-adenosylmethionine giving 50% inhibition wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…The lack of feedback inhibition of homoserine O-acetyltransferase activity is highly significant since the concentrations of inhibitors in the reaction were at least 10 times higher than the K m values for the substrates, which were 0.46 Ϯ 0.07 and 0.2 Ϯ 0.06 mM for homoserine and acetyl coenzyme A, respectively. This result for the MetX Leptospira enzyme is in contrast to the feedback inhibition by methionine and S-adenosylmethionine found for the similar enzymes from Bacillus subtilis, Bacillus polymyxa, and Brevibacterium flavum (3,21,23).…”
contrasting
confidence: 56%
“…The lack of feedback inhibition of homoserine O-acetyltransferase activity is highly significant since the concentrations of inhibitors in the reaction were at least 10 times higher than the K m values for the substrates, which were 0.46 Ϯ 0.07 and 0.2 Ϯ 0.06 mM for homoserine and acetyl coenzyme A, respectively. This result for the MetX Leptospira enzyme is in contrast to the feedback inhibition by methionine and S-adenosylmethionine found for the similar enzymes from Bacillus subtilis, Bacillus polymyxa, and Brevibacterium flavum (3,21,23).…”
contrasting
confidence: 56%
“…(2) This enzyme has not yet been well characterized except for a few bacteria (16,22,26,27). Shiio and colleagues (16,22) have recently reported on feedback control by the end product methionine in the case of the enzyme from Brevibacterium flavum.…”
mentioning
confidence: 99%
“…Shiio and colleagues (16,22) have recently reported on feedback control by the end product methionine in the case of the enzyme from Brevibacterium flavum. Wyman et al have described purification of the enzyme to near homogeneity (26) and also its regulation in whole cells (27) of Bacillus polymyxa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydratase I might possibly be converted into dehydratase I1 by desensitization during extraction from E. gracilis cells like in homoserine 0-acetyltransferase (Shiio & Ozaki, 1981), but this is not the case. We found that unusual accumulation of isoleucine during the growth inhibition by threonine was due to an insufficiently controlled formation of 2-oxobutyrate from exogenous threonine (Oda et al, 1982b).…”
Section: Discussionmentioning
confidence: 99%